Some medicinal plants as natural anticancer agents - Pandey, Govind; S, Madhuri (Pharmacognosy Reviews)
India is the largest producer of medicinal plants and is rightly called the “Botanical garden of the World”. The medicinal plants, besides having natural therapeutic values against various diseases, also provide high quality of food and raw materials for livelihood. Considerable works have been done on these plants to treat cancer, and some plant products have been marketed as anticancer drugs, based on the traditional uses and scientific reports. These plants may promote host resistance against infection by re-stabilizing body equilibrium and conditioning the body tissues. Several reports describe that the anticancer activity of medicinal plants is due to the presence of antioxidants in them. In fact, the medicinal plants are easily available, cheaper and possess no toxicity as compared to the modern (allopathic) drugs. Hence, this review article contains 66 medicinal plants, which are the natural sources of anticancer agents.
Keywords: Cancer; medicinal plants; natural anticancer agents; antioxidants